2022
DOI: 10.21203/rs.3.rs-1546784/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation and characterization of marine actinomycetes – bioprospecting for antimicrobial, antioxidant and anticancer properties

Abstract: The novel therapeutic agents are frequently produced from marine actinomycetes and are still being explored due to their vast diversity. In this research, we isolated five marine actinomycetes (BN01, BN12, BN13, BN14 and GB15) from the soil sediments of the coastal region of Chennai, Tamil Nadu, India. The morphological and physicochemical properties of the isolates were characterized. The 16S rRNA sequencing analysis showed that the isolates were belonging to two genera namely Streptomyces and Saccharopolyspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Detailed research has been conducted on the isolation, identification, and taxonomy of actinobacteria from various marine environments. Actinobacteria have attracted for their potential to produce novel compounds for the treatment of various diseases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed research has been conducted on the isolation, identification, and taxonomy of actinobacteria from various marine environments. Actinobacteria have attracted for their potential to produce novel compounds for the treatment of various diseases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 Soil sediments from the Bay of Bengal shore near Chennai, Tamil Nadu, India, were chosen and dried for a week in sterile conditions. 60 Soil samples from the saltpan of Ennore were collected in sterile polythene bags and preserved at 4°C for further study. 61 South Andaman Island of India, noted for mangrove vegetation offered four marine sediment samples which were taken from the Bay of Bengal coast and the Andaman Sea coast.…”
Section: Collection Of Marine Samplementioning
confidence: 99%
“…Further, fluconazole (50 µg/mL) was dispensed in media to inhibit the fungal growth. 60 The importance of salt concentration in isolating marine actinomycetes was studied, the absence of NaCl in the culture medium yielded little or no growth, on the other hand isolates were able to grow in 3% NaCl, some isolates were able to grow in 10% NaCl. Further, the study concluded that none of the organisms grew on the media containing salt concentration upto 14%.…”
Section: Treatment Of Marine Samplesmentioning
confidence: 99%